Research Trends in Sustainable Entrepreneurship Based on Bibliometric Analysis of Scopus Publications for the Period 2012–2024 - Loso Judijanto (Westscience Press, 2026)
Sustainable entrepreneurship has emerged as an important research domain that integrates entrepreneurial activities with environmental and social sustainability goals. The growing global concern regarding climate change, resource scarcity, and inclusive economic development has increased scholarly attention to this field. This study aims to analyze the development and research trends of sustainable entrepreneurship through a bibliometric approach. The analysis is based on publications indexed in the Scopus database during the period 2012–2024. Bibliometric techniques were employed using VOSviewer to visualize scientific collaboration networks and thematic structures within the literature. The results indicate a significant growth in publications related to sustainable entrepreneurship, reflecting increasing academic interest in the intersection between entrepreneurship and sustainable development. Co-authorship and country collaboration analyses reveal that research in this field is supported by international collaboration networks, with countries such as the United States, the United Kingdom, and India playing important roles in knowledge production. Keyword co-occurrence analysis shows that entrepreneurship, sustainable development, and sustainability form the core concepts of the research field, while emerging themes such as circular economy, sustainable development goals (SDGs), entrepreneurship education, and digital technologies indicate evolving research directions.